IgG sialylation occurs in B cells pre antibody secretion - Werner, Anja; Hanić, Maja; Zaitseva, Olga O.; Lauc, Gordan; Lux, Anja; Nitschke, Lars; Nimmerjahn, Falk (Frontiers in Immunology, 2024)
Sialic acids as terminal sugar residues on cell surface or secreted proteins have many functional roles. In particular, the presence or absence of α2,6-linked sialic acid residues at the immunoglobulin G (IgG) Fc fragment can switch IgG effector functions from pro- to anti-inflammatory activity. IgG glycosylation is considered to take place inside the plasma blast/plasma cell while the molecule travels through the endoplasmic reticulum and Golgi apparatus before being secreted. However, more recent studies have suggested that IgG sialylation may occur predominantly post-antibody secretion. To what extent this extracellular IgG sialylation process contributes to overall IgG sialylation remains unclear, however. By generating bone marrow chimeric mice with a B cell-specific deletion of ST6Gal1, the key enzyme required for IgG sialylation, we now show that sialylation of the IgG Fc fragment exclusively occurs within B cells pre-IgG secretion. We further demonstrate that B cells expressing ST6Gal1 have a developmental advantage over B cells lacking ST6Gal1 expression and thus dominate the plasma cell pool and the resulting serum IgG population in mouse models in which both ST6Gal1-sufficient and -deficient B cells are present.